Perlindungan Hukum Terhadap Investasi Kripto Pada Aplikasi Tokocrypto - Akhmad Fairuz Badi Uyun; Hardian Iskandar (UNES Law Review, 2023)
The purpose of this research is to provide knowledge about the security of cryptocurrency and the laws that protect it in Indonesia. In addition, it is also an insight to be aware of fraud. This research takes a normative and statutory juridical method approach through some literature related to the problem of this research by understanding the laws that have been collected. Tokocrypto is a trading and investment platform where the process is based on agreements and regulations submitted by Tokocrypto. Regarding safety issues and customer protection, it has been explained in BAPPETI No. 11 of 2022 (Determination of the Crypto Asset Trading List on the Crypto Asset Physical Market), Regulations, Bappebti Regulation No. 2 of 2019 concerning the Implementation of the Commodity Physical Market on the Futures Exchange, Bappebti Regulation No. 5 of 2019 concerning Technical Provisions for the Implementation of the Crypto Asset Physical Market on the Futures Exchange. Tokocrypto assets are officially processed by parties who work and cooperate with Treasury with the permission of BAPPETI No. 001/BAPPEBTI/CP-AK/11/2019 dated November 18.